PERAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING MEMPENGARUHI KINERJA KARYAWAN - CANDRA KUSUMA DEWI, NOVIA; FRIANTO, AGUS (Jurnal Ilmu Manajemen (JIM), 2020)
This research aims to determine and explain the effect of the work environment on employee performance through job satisfaction as an intervening variable on PT PLN (Persero) UP3 Bojonegoro. This research is a type of causal research that uses a quantitative approach to permanent employees and the sampling technique uses saturated samples with an amount sample of 48 permanent employees. The statistical analysis used in this study was Partial Least Square (PLS) with the help of Smart PLS 3.0 software. The work environment has a positive and significant effect on employee performance. The work environment has a positive and significant effect on job satisfaction. Job satisfaction has a positive and significant effect on employee performance. Job satisfaction can mediate the influence of the work environment on employee performance.Keywords: employee performance; job satisfaction; work environment.